The Web-Based Government Information System ImplementationModel for Village Government - Nurhadi, Nurhadi; Hertati, Diana (Archives of Business Research, 2019)
In order to improve the accountability of village financial management and encourage people to actively participate in village development, a web-based information system is needed. This study aims to describe the conceptual specifications of a web-based village government information system and guidelines for the use of web-based village government information systems. The study was conducted in two villages and two sub-districts, namely Tambak Oso village, Waru sub-district and Sedati village, Sedati sub-district, Sidoarjo regency. Data collection is done by interviews and documentation. The method of data collection is done by using interviews, focused group and discussion. Data analysis was performed using qualitative analysis. The results of the study show that Segoro Tambak and Tambak Oso villages have carried out village financial management in accordance with the principles of transparency and accountability, but the two villages have not fully complied with the regulations that have been determined. Some of the obstacles faced include the ineffectiveness of fostering village apparatus, lack of supervision, lack of personnel, and a lack of understanding of the village apparatus against applicable regulations.